Novel Herbal Topical Patch Containing Curcumin and Arnica montana for the Treatment of Osteoarthritis - Kriplani, Priyanka; Guarve, Kumar; Baghel, Uttam S. (Current Rheumatology Reviews, 2020)
Background: Osteoarthritis (OA) ranks fifth among all forms of disability affecting 10% of the world population. Current treatments available are associated with multiple side effects and do not slow down the progression of the disease. Moreover, no such effective treatment is available to date in various systems of medicine to treat osteoarthritis. Curcumin and Arnica have shown evident clinical advances in the treatment of osteoarthritis. Objective: The aim of the present study was to design, optimize and characterize novel herbal transdermal patches of curcumin and Arnica montana using factorial design. Methods: A multiple factorial design was employed to investigate the effect of hydroxypropyl methyl cellulose, ethyl cellulose and jojoba oil on elongation and drug release. Transdermal patches were evaluated by FTIR, DSC, FESEM, ex vivo drug permeation, anti osteoarthritic activity and analgesic activity. Results: Independent variables exhibited a significant effect on the physicochemical properties of the prepared formulations. The higher values of drug release and elongation were observed with the higher concentration of hydroxypropyl methylcellulose and jojoba oil. Anti osteoarthritic activity was assessed by complete Freund's adjuvant arthritis model; using rats and analgesic activity by Eddy's hot plate method, using mice. Combination patch exhibited good anti osteoarthritic and analgesic activity as compare to individual drug patches. Conclusion: The design results revealed that the combination patch exhibited good physicochemical, anti osteoarthritic and analgesic activity for the treatment of osteoarthritis in animals. More plants and their combinations should be explored to get reliable, safe and effective formulations that can compete with synthetic drugs.
Keywords: curcumin